2008
DOI: 10.1038/sj.jid.5701069
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-Binding EGF-Like Growth Factor Is Induced by Disruption of Lipid Rafts and Oxidative Stress in Keratinocytes and Participates in the Epidermal Response to Cutaneous Wounds

Abstract: Epidermal homeostasis and repair of the skin barrier require that epidermal keratinocytes respond to alterations of their environment. We report that cellular stress with methyl-beta-cyclodextrin (MBCD), a molecule that extracts membrane cholesterol and thereby disrupts the structure of lipid rafts, strongly induces the synthesis of heparin-binding EGF-like growth factor (HB-EGF) in keratinocytes through the activation of p38 mitogen-activated protein kinase. Interesting parallels between lipid raft disruption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 58 publications
3
58
0
Order By: Relevance
“…ester and various other stress stimuli on cultured cells are able to induce HB-EGF mRNA levels and the shedding of proHB-EGF into soluble HB-EGF 26 . In addition to EGF, IL-8 is also active as a mitogen for epithelial and endothelial cell proliferation 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ester and various other stress stimuli on cultured cells are able to induce HB-EGF mRNA levels and the shedding of proHB-EGF into soluble HB-EGF 26 . In addition to EGF, IL-8 is also active as a mitogen for epithelial and endothelial cell proliferation 26 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to EGF, IL-8 is also active as a mitogen for epithelial and endothelial cell proliferation 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Since MAPK p38 plays major roles in cellular responses to environmental and physiological stresses [14,15,20,32] and MAPK ERK 1/2 promotes cellular proliferation needed for tissue reconstruction [24], phosphorylation of both MAPK's was investigated in our model. RHE was exposed for 1, 2, 4, 8 or 22 h to DNFB (0.250 mg/ml) as a prototype sensitizing chemical, then tissue extracts were analyzed by Western blot in order to detect phosphorylated forms of p38 and ERK 1/2 MAPK's (Fig.…”
Section: Exposure Of Rhe To Sensitizing Chemicals Induces Early Transmentioning
confidence: 99%
“…25,26 Of interest in the current work is the possible role of the physical state of lipid in the receptor environment on the control of EGFR function. Several studies addressing this issue have suggested receptor localization in lipid rafts, [17][18][19][20]27 cholesterol enriched domains involved in signal transduction. Pike et al 17 reported that the EGFR-enriched lipid rafts are augmented in lipid classes that differ from those identified by the classical Triton X-100 extraction procedure that first defined lipid rafts.…”
Section: Discussionmentioning
confidence: 99%
“…The initially impaired barrier was restored to near normal at six months postgrafting. In additional studies by several groups over the past decade, [17][18][19][20] the putative role of lipid rafts in controlling the function of cell signaling molecules, involving the epidermal growth factor receptor (EGFR), has been investigated through biochemical and molecular approaches. EGFR controls keratinocyte proliferation and motility.…”
Section: Introductionmentioning
confidence: 99%